Effect of transmeridian travel and jetlag on mood disorders: Evidence and implications. (March 2016) - Inder, Maree L; Crowe, Marie T; Porter, Richard
Objectives: Given the sensitivity of individuals with mood disorders to circadian disruption, transmeridian travel would likely be a high-risk endeavour leading to onset or relapses in mood. A systematic review was undertaken to identify the evidence of the impact of transmeridian travel on people with mood disorders. Methods: Databases search included the following: CINAHL, MEDLINE, PsycINFO and manual searching using the keywords jetlag, transmeridian travel, circadian rhythm disruption, mood disorder, bipolar, major depression, seasonal affective disorder, depression, mania and hypomania. Results: Only three studies were identified that related to transmeridian travel and jetlag in people with mood disorders. There is some suggestion that transmeridian travel does appear to precipitate mood episodes with an increased rate of episodes of depression with westward compared with an increased rate of manic/hypomanic episodes with eastward travel. Individuals with a previous history of mood disorder appear to be more vulnerable if adherence to medication is compromised. Conclusion: Given the limited evidence that transmeridian travel precipitates mood episodes, this poses difficulties in identifying suitable ways to mitigate the effects of transmeridian travel in mood disorders. However, in the absence of mood-specific guidelines, some guidance can be given based on our current understanding of the relevance of circadian disruption to both jetlag and mood disorders. Further research is required to identify more focused strategies to mitigate the impact of transmeridian travel for individuals with mood disorders.